Special Issue: the International Conference on Upstream Energy and digitalization (ICU-PERTAIN) 2022 - Tirta Rona Mayangsari; Harya Dwi Nugraha; Fiki Hidayat (Journal of Earth Energy Engineering, 2023)
This is an international conference organized by Universitas Pertamina collaborated with Universitas Islam Riau as publishing partner through Journal of Earth Energy Engineering (JEEE) and Journal of Geoscience, Engineering, Environment, and Technology (JGEET). The theme of the International Conference on Upstream Energy and digitalization (ICU-PERTAIN) 2022: “Upstream Industries and 4.0 things to overcome the challenges in a low carbon world”. This theme means identifying the key challenges and opportunities of implementation upstream technology and utilization of big data, data science, machine learning, IoT, and many more to achieve national production target and strive to energy transition.